Peningkatan Hasil Belajar IPS Melalui Penggunaan Media Gambar Pada Siswa Kelas IV SD Inpres Bertingkat Mamajang I Kota Makassar - Afni, Nur (STKIP Andi Matappa Pangkep, 2021)
This study aims to determineincreasing social studies learning outcomes through the use of image media in class students IV SD. The approach in this research is qualitative with the research subjects being teachers and 25 grade IV SD students. Data collection techniques used in this study were observation, tests. While the data analysis used was qualitative and quantitative. In the implementation of observations of teachers in cycle I had not fully implemented the use of image media well, while in cycle II the teacher had implemented the use of image media well, then in student observations it was found that the average value of student learning outcomes in social studies lessons was in a low category (R). Whereas in the first cycle the average value of student learning outcomes was in the medium category (S) and the second cycle the average value of student learning outcomes got the high category (T). From the research findings and the provision of teaching and learning actions, it can be concluded that with the use of image media, social studies learning outcomes increase in grade IV SD students Mamajang 1 Tiered Presidential Instruction of Makassar City increased.